Distance Protection Test on Siemens SIPROTEC Digital Twin with MATLAB Simulink Test Grid - Alkhalili, Hassan; Löbel, Jonathan; Jäger, Johann (PESS 2023 – IEEE Power and Energy Student Summit, 2024)
Due to the strong expansion of renewable energies, the number of power converters in the electrical grid is increasing strongly. Voltage source converters (VSCs) in particular play a significant role in this. The integration of VSCs poses unique challenges for network protection, and understanding the behavior of the protection devices in this context is crucial for ensuring reliable operation. In order to easily test this influence, a test setup was built, which is presented in this article. A simple test grid was set up in MATLAB Simulink. This consists of a VSC connected to an external grid via an LCL filter and a transmission line. The VSC is designed with a current control that works in PQ-mode. Voltages and currents are measured at the grid connection point and fed into the Siemens Siprotec Digital Twin via a CSV-to-COMTRADE script. The protection settings were parameterised in DIGSI 5. For verification, a ground fault and a two-phase-fault were simulated in the test network. The protection device was set with a distance protection with three different pickup modes. The classic settings of the overcurrent pickup mode did not lead to any trigger. The voltage dependent current pickup U/I and voltage and angle-dependent current pickup U/I/phi did trigger in all cases. With the test setup, the influence of the VSC control on the mains protection can be tested very easily and the protection or the control can be adjusted accordingly to guarantee a safe main